LANDSCAPE INFOGRAPHIC DESIGN - Krejčí, Markéta; Hradilová, Iva (European Scientific Journal, ESJ, 2014)
This lack of understanding is caused by the urban environment complexity as cities and towns cannot adapt to the current situation in which people overcome larger distances more easily and faster. The public space becomes hard to live in because individuals‘ abilities to identify the surrounding environment are a basic factor of their involvement in social relationships. The landscape infographics is to focus on the objects in the space that help orientation in the complicated urban environment and that are presented in the form of garden design and landscape architecture features.An orientation system does not necessarily mean information boards only. The main feature of an orientation system concept can be elements of landscape infographics, which can help find the right direction or place. Landscape infographics with its means forms natural orientation aids that are easily discernible without complicated cognitive processes due to their temporal and spatial convergence. As regards the present requirement of polyfunctional structure, landscape infographics uses orientation entities that use a clear form to define the location and segment the path. Spatial orientation necessitates the ability to read the complicated layered urban environment. The human need to identify with the surroundings in its everyday form and the ability to create an imaginary diagram of places in the surroundings is a primary feature that affects the individual‘s involvement in social relationships. The project of landscape infographic design with the current graphic design methods and means in the public space; they are processed in relation to potential of landscaping methods applicable to the creation of good readability of urban places.